2017
DOI: 10.1039/c7ee01889d
|View full text |Cite
|
Sign up to set email alerts
|

Flexibly assembled and readily detachable photovoltaics

Abstract: A flexibly assembled and readily detachable perovskite solar cell is introduced and paves the way for innovative cell design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Organometal halide perovskites (OHPs) have good solubility due to their ionic nature, which enables low-temperature solution processes for perovskite solar cells (PSCs) manufacturing, including screen printing, blade coating, slot-die coating [1][2][3][4] . These manufacturing methods are well compatible with roll-to-roll (R2R) large-scale manufacturing processes to fabricate lightweight flexible PSCs, which can significantly reduce the manufacturing cost and show strong potential for application in wearable electronics, portable charger, flying objects, etc.…”
mentioning
confidence: 99%
“…Organometal halide perovskites (OHPs) have good solubility due to their ionic nature, which enables low-temperature solution processes for perovskite solar cells (PSCs) manufacturing, including screen printing, blade coating, slot-die coating [1][2][3][4] . These manufacturing methods are well compatible with roll-to-roll (R2R) large-scale manufacturing processes to fabricate lightweight flexible PSCs, which can significantly reduce the manufacturing cost and show strong potential for application in wearable electronics, portable charger, flying objects, etc.…”
mentioning
confidence: 99%
“…After the optimization of the elastic interface by adding t‐BP and Li‐TFSI, Figure b shows an improved PCE (13.49%), with an open‐circuit voltage ( V OC ) of 1.1 V, a short‐circuit current ( J SC ) of 21.53 mA cm −2 , and a FF of 0.57. The mechanism using t‐BP and Li‐TFSI as additive has been well addressed in our previous papers . The addition of 4‐tert‐butylpyridine (TBP) and Li salt can effectively retard interfacial charge recombination, which is conductive to enhance V OC and FF, as can be confirmed by the parameters in Table .…”
Section: Photovoltaic Performance Outcomes Of Cells Fabricated Using mentioning
confidence: 68%
“…Zhou and co‐workers used the transfer‐lamination technique to place dried PEDOT:PSS film layer on top of the CH 3 NH 3 PbI 3 perovskite film . Wang et al reported flexibly assembled and readily detachable photovoltaics that were also made by two electrodes . It is widely accepted that the crucial step determining the device performance is the formation of intimate interfacial electrical structure between the laminated parts which is the main region where the internal dynamic process of the cells occurs.…”
Section: Photovoltaic Performance Outcomes Of Cells Fabricated Using mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Shi and co‐workers designed a flexibly assembled and readily detachable PSC with PEDOT:PSS electrode (Figure 16c). [ 154 ] By introducing tert ‐butylpyridine and Li salt in PEDOT:PSS layer, an improved interfacial contact was achieved to facilitate the hole transport and suppress charge combination, thus resulting in a PCE value of 14.62%. Meanwhile, the device could withstand repeated assembly and disassembly tests for more than 100 cycles without any loss in PCE.…”
Section: Polymer Electrodesmentioning
confidence: 99%